Social protection of ATO/OUF veterans and their families at the community level - Kravchenko, Oksana; Kucher, Halyna (Social work and education, 2022)
The article describes the Uman territorial community as a social community thanks to its extensive system of social institutions, the implementation of the best international practices, the constant expansion of the social welfare spectrum, the focus on the needs of every individual and the necessity to satisfy those needs according to state standards. At the same time, the community establishes a social protection system (social services and social security) for ATO/OUF participants and their families. For this purpose, four social protection programs for 2021-2025 period have been developed and approved for ATO/OUF participants and the families of the fallen (integrated health, welfare, social security programs, adaptation, psychological rehabilitation, vocational training (retraining) for the anti-terrorist operation participants, the families of the Heavenly Hundred, the victims of the Revolution of Dignity, and fighter - volunteers; housing provision for 2021-2025 period for the participants of the anti-terrorist operation/operation of the joint forces and volunteer fighters who participated in the protection of territorial integrity and state sovereignty in the East of Ukraine and for their family members; "Care" social assistance for 2021-2027; national-patriotic education for children and youth for 2021-2025); an Assistance Center has been established for the Participants of the Anti-Terrorist Operation; there has been established the division of military personnel adaptation, assistance for the participants of the anti-terrorist operation, deportees and labor migrants; benefits and social guarantees are provided to participants (utility reimbursement , free meals in preschool and secondary schools for children of ATO participants, rehabilitation in a summer health camp, provision of a one-time financial assistance, free public transportation within the city, purchase of cold water meters, free education for children of the fallen ATO participants in art schools, etc.), medical and psychological assistance is provided in "Harmony" Rehabilitation Complex for People with Special Needs, professional rehabilitation, sports rehabilitation, employment, informational and explanatory work, etc. are provided.